Simulation of a collector using waste heat energy in a solar chimney power plant system - Azeemuddin, (WITPress, 2013)
Rare techniques have been proposed for twenty four hour operation of a solar chimney power plant (SCPP). In this study, another technique is suggested by utilizing waste heat energy in the form of flue gases flow in conduits within the solar collector. The process of the heat and fluid flow within the collector were simulated using ANSYS software. The predicted performance and enhancement of the collector are presented and discussed. The results show a significant increase in the overall performance of the solar chimney power plant. At 1000 W/m2 solar radiation, the collector temperature rise is from 19 to 23 K, the updraft velocity is increased from 15.6 m/s to 17.1 m/s, the power output increased from 50.1 kW to 66.1 kW and the efficiency is improved from 0.116 to 0.144. Although the technique contributes to the performance enhancement of the SCPP, it also contributes to the reduction of global warming by reduction of the exhausted flue gases temperature. Â© 2013 WIT Press.